2016
DOI: 10.1038/mi.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

Role of mannose-binding lectin in intestinal homeostasis and fungal elimination

Abstract: Mannose-binding lectin (MBL) is a soluble lectin of the innate immune system that is produced by the liver and secreted into the circulation where it activates the lectin complement pathway, enhances phagocytosis of microorganisms by leukocytes, and modulates inflammation. MBL can recognize patterns on the surface of different pathogens, including Candida albicans. Our aims were to investigate whether MBL is expressed in the gut epithelium and to examine its effect on the modulation of intestinal inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 47 publications
1
60
0
Order By: Relevance
“…Similarly, in a model of colitis-associated cancer induced by dextran sodium sulfate (DSS) along with azoxymethane, C3-deficient mice had reduced IL-17A production in myeloid cell populations and were therefore less susceptible to tumor development (48). In contrast, MBL-deficient mice had enhanced intestinal IL-17A and IL-23 mRNA levels in a DSS colitis model (49). The differential effects of complement in these two models may reflect differences in the time points analyzed (day 60 versus day 14), differences in the specific mouse mutants analyzed, or other differences between mouse colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a model of colitis-associated cancer induced by dextran sodium sulfate (DSS) along with azoxymethane, C3-deficient mice had reduced IL-17A production in myeloid cell populations and were therefore less susceptible to tumor development (48). In contrast, MBL-deficient mice had enhanced intestinal IL-17A and IL-23 mRNA levels in a DSS colitis model (49). The differential effects of complement in these two models may reflect differences in the time points analyzed (day 60 versus day 14), differences in the specific mouse mutants analyzed, or other differences between mouse colonies.…”
Section: Discussionmentioning
confidence: 99%
“…We also checked public databases to see the effect of pioglitazone on the expression of these 14 glycose metabolism genes in other epithelial cell populations. There is only one publicly available gene expression data set (GSE68852) studying the effects of pioglitazone treatment on the transcriptomic profile of intestinal epithelial cells (Caco-2 cells) (19). We compared our results with those of that study and found that only 2 of the 14 validated lung brushing glucose metabolism genes were downregulated in the Caco-2 cells by pioglitazone treatment; these were NUP107 (fold change = -1.4, P = 0.01) and VCAN (fold change = -1.9, P = 3.5 × 10 -5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several chronic inflammatory diseases, such as colitis, Crohn's disease, Kawasaki disease, and rheumatoid arthritis (RA), have been reported to be significantly associated with CD206, CD209, and Dectin-1 [68]. However, in BD, the correlation of CLR has not been published at all except mannose-binding lectin, one kind of soluble protein of CLR [9].…”
Section: Introductionmentioning
confidence: 99%